Comparing great apes' and children's ability to reason by analogy - Hribar, Alenka (2011)
Analogical reasoning, reasoning about relational similarity, is often considered to be one of the hallmarks of human cognition. However, although analogical reasoning has been studied extensively in humans, we know very little about this cognitive ability in our phylogenetically closest living relatives, the other great apes. Most of the studies to date that have assessed analogical reasoning in nonhuman animals have used a single paradigm and have focused on the relation of identity/non-identity. In addition, only one study has directly compared analogical reasoning ability of great apes and children. Therefore, my PhD project had two main goals: firstly, to investigate great apes’ flexibility in analogical reasoning using a novel paradigm; secondly, to compare great apes’ analogical reasoning with that of human children. The task that I employed was a spatial mapping task where an individual is required to find a reward in an array of three cups, after observing a reward being hidden in a different array of three cups. To obtain a reward, the individual needs to choose the cup that is in the same relative position as the baited cup in the other array.The results of the first study showed that great apes have some rudimentary ability to engage in analogical reasoning. However, the results also suggested that the apes might have employed a different approach and encoded different type of spatial relations than I expected them to. More specifically, the apes appeared to encode the baited cup in relation to a nearby landmark, rather than in relation to the other cups present in the array. The second study confirmed the assumption that apes encoded the location of the baited cup in terms of its relationship to a nearby landmark. In the third study presented here, I investigated whether 4- and 5-year-olds - that have previously been shown to be capable of mapping spatial relations - would spontaneously engage in relational mapping, without any explicit instruction to do so. In addition, I was interested to see whether children, like apes, would show a preference for mapping between item arrays using landmark cues. Indeed Study 3 has provided very similar results to Study 1: children, like apes, did not appear to encode and map the relative position of the baited cup across the two arrays. And therefore it is likely that children employed the same mapping strategy as apes.
Keywords: Hochschulschrift